Mengimplementasikan Amsal 22:6 dalam Penerapan Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Kristen di Sekolah - Firmansah, Endik; Rahel, Rahel; Sukrisno, Aji (Sekolah Tinggi Alkitab Batu, Malang, 2023)
This research is motivated by the implementation of an independent curriculum in schools which has received various responses, including agreeing and disagreeing. The author believes that every teacher, especially Christian Religious Education teachers, must be ready for every policy from the government as a form of obedience to the government as God's representative. This research uses a qualitative method which uses several references from books, journals and also past and ongoing phenomena faced by the researcher as a Christian teacher at school. The implementation of an independent curriculum, which researchers understand as a curriculum that places more emphasis on learning patterns that are adapted to students' talents and interests, is not at all contrary to God's Word. Furthermore, after finding this meaning, this research continued by implementing it in the learning process in schools with the hope that every Christian Education teacher in schools can carry out their duties with more spiritual responsibility to God because they see that the implementation of the independent curriculum is not just proof of obedience to the government but also proof from obedience to God. Keywords: Independent Curriculum, Educate Young People, The Right Way. AbstrakPenelitian ini dilatarbelakangi oleh diterapkannya kurikulum merdeka di sekolah yang telah mendapatkan berbagai respon antara setuju dan tidak setuju. Penulis berpendapat bila setiap guru secara khusus guru Pendidikan Agama Kristen harus siap kepada setiap kebijakan dari pemerintah sebagai bentuk ketaatan kepada pemerintah sebagai wakil Tuhan. Penelitian ini menggunakan metode kualitatif yang menggunakan beberapa referensi buku, jurnal dan juga fenomena di masa lampau dan yang masih berjalan yang dihadapi oleh peneliti sebagai seorang guru agama Kristen di sekolah. Penerapan kurikulum merdeka yang dipahami peneliti sebagai kurikulum yang lebih menekankan secara sederhana kepada pola pembelajaran yang disesuaikan dengan bakat dan minat siswa, tidak sama sekali bertentangan dengan Firman Tuhan. Selanjutnya, setelah menemukan makna tersebut, penelitian ini dilanjutkan dengan mengimplementasikannya dalam proses pembelajaran di sekolah dengan harapan setiap guru Pedidikan Agama Kristen di sekolah dapat melaksanaan tugasnya dengan lebih bertanggungjawab secara rohani kepada Tuhan karena melihat implementasi kurikulum merdeka tidak sekadar bukti ketaatan kepada pemerintah tetapi juga bukti dari ketaatan kepada Tuhan. Kata kunci: Kurikulum Merdeka, Didiklah Orang Muda, Jalan Yang Patut